Kompetensi Pengadilan Agama dalam Menangani Perkara Warisan Beda Agama (Analisis Perkara 1854/Pdt.G/2013/PA.Plg) - Muhammad, Hanifah Salma; Ibrahim, Malik (MAHAKIM Journal of Islamic Family Law, 2023)
This article discusses the competence of religious courts in adjudicating disputes over interfaith inheritance between Muslims and non-Muslims. This can happen inseparably from the social and cultural conditions of people in Indonesia who are pluralism with various backgrounds such as ethnicity, customs, different languages, and belief or religious factors. But on the other hand, there are differences in views between the fuqaha regarding the heritage of different religions. If the heir and heir, both the heir as the plaintiff and the defendant, have differences in religion, then the practice of law enforcement in the court against the inheritance case creates a dispute over competence between the religious court and the district court. This study examines through legislation, legal literature in accordance with the research being discussed and uses Islamic law to answer the author's problem formulation by analyzing decision number 1854 / Pdt.G / 2013 / PA.Plg. The results of the research that can be concluded are that when viewed from a juridical point of view, religious courts are authorized to adjudicate cases of disputes over inheritance between religions. This can happen because it is based on jurisprudence 51K/AG/1999. The function of jurisprudence can be used as the best way given by judges to communities that have family pluralism as a solution in resolving cases of inheritance disputes between religions. However, when viewed from the normative side of Islamic law, religious courts are authorized to adjudicate inheritance disputes with parties of different religions. This can happen because it is based on the interpretation of Yusuf Al-Qardawi and the ijtihad of the supreme court for a sense of justice for families whose pluralism of beliefs. The inheritance is not counted as heirs but is counted as a mandatory will of no more than 1/3 part.